Non-invasive MRI Studies of Ventilatory and Cardiovascular Performance in Edible Crabs Cancer pagurus During Warming Under Elevated CO2 Levels - Maus, Bastian; Gutsfeld, Sebastian; Bock, Christian; Pörtner, Hans-Otto (Frontiers in Physiology, 2021)
The thermal tolerance of marine decapod crustacea is defined through their capacities for oxygen uptake and distribution. High ambient CO2 levels were previously shown to reduce haemolymph oxygen levels at enhanced cardiac performance during warming. This study investigated impacts of warming under two CO2 levels on ventilation and haemolymph circulation in edible crabs Cancer pagurus. It also highlights changes in the ventilatory and cardiac pauses displayed by Decapoda under routine metabolism. Animals were exposed to step-wise, sub-critical warming (12-20°C over five days) under control (470 µatm) and high (1350 µatm) water PCO2. Flow-through respirometry was combined with magnetic resonance imaging and infra-red photoplethysmography to allow for simultaneous, non-invasive measurements of metabolic rates (MO2), ventilation and cardiovascular performance. Crabs spent significantly more time in a low MO2 state (metabolic pause), when experiencing high CO2 conditions above 16°C, compared to normocapnic warming. Heart rates leveled off beyond 18°C at any CO2 level. Cardiac output continued to increase with high-CO2-warming, due to elevated cardiac stroke volumes. Consequently, temperature-dependent branchial haemolymph flow remained unaffected by CO2. Instead, a suppressing effect of CO2 on ventilation was found beyond 16°C. These results indicate constrained oxygen uptake at stable cardiovascular performance in a decapod crustacean.